Anti-Mullerian Hormone (AMH) and adenomyosis: Mini-review of literature of the last 5 years - Gulino, Ferdinando Antonio; Dilisi, Valentina; Capriglione, Stella; Cannone, Francesco; Catania, Francesco; Martire, Francesco Giuseppe; Tuscano, Attilio; Gulisano, Marianna; D’Urso, Valentina; Di Stefano, Alessandra; Cimino, Monia Caterina; Filippini, Maurizio; et al. (Frontiers in Endocrinology, 2022)
Introduction Adenomyosis is a form of endometriosis characterized by the presence of endometrial tissue in the myometrium. The correlation between anti-Mullerian hormone (AMH) expression and adenomyosis is unclear. Few studies investigated this possible correlation with promising results. The aim of this mini-review is to illustrate the potential prognostic and therapeutic role of AMH in adenomyosis. Materials and methods A study protocol was completed conforming to the Preferred Reporting Items for Reviews and Meta-Analyses (PRISMA) guidelines for systematic reviews. We performed an electronic databases search from each database’s inception from August 2017 to August 2022 for full-text articles and published abstracts. For database searches, the following main keywords were the following text words: “adenomyosis” or “uterine endometriosis” [Mesh] AND “AMH” or “anti-mullerian hormone”. Results From the literature search, 8 abstracts of studies were retrieved and independently screened for inclusion by three authors. It was found that the most common therapeutic strategies (such as adenomyomectomy and high-intensity focused ultrasound (HIFU) do not alter AMH levels. Moreover, a higher expression of the AMH receptor II was observed in adenomyotic tissue, hence a possible therapeutic use of AMH was hypothesized. Conclusion The available evidence shows an unclear relationship between adenomyosis and AMH. Probably, women with adenomyosis have lower levels of AMH and the surgical treatment (adenomyomectomy, HIFU) does not alter this characteristic, therefore in all of them, ovarian function is not influenced.